2012
DOI: 10.1186/2251-6581-11-22
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between beta-globin gene carrier state and insulin resistance

Abstract: ObjectiveTo assess the relationship between being beta globin gene carrier and developing insulin resistance.MethodsThis study was conducted on 164 subjects including 82 healthy ones and 82 patients with beta thalassemia minor (microcytosis (MCV <80 fl) and hypochromia (MCH <25 pg) and HbA2 ≥ 3.5% using HPLC). Fasting blood glucose (FBS) values of 100–125 mg/dl were considered as impaired fasting glucose, and above 125 mg/dl as diabetes mellitus. Two hours After 75 gram glucose load(GTT), blood sugar level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 16 publications
1
14
2
1
Order By: Relevance
“…BTM is associated with various metabolic disturbances (12)(13)(14) , including insulin resistance (12,13) . Research suggests that chronic microcytic erythrocytic hemolysis in BTM patients leads to oxidative stress and liver inflammation, which then lead to insulin resistance (12,14) . Gozashti et al noted BTM is associated with high prevalence of carbohydrate-related metabolic disorders which result liver inflammation and subsequent insulin resistance (15) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BTM is associated with various metabolic disturbances (12)(13)(14) , including insulin resistance (12,13) . Research suggests that chronic microcytic erythrocytic hemolysis in BTM patients leads to oxidative stress and liver inflammation, which then lead to insulin resistance (12,14) . Gozashti et al noted BTM is associated with high prevalence of carbohydrate-related metabolic disorders which result liver inflammation and subsequent insulin resistance (15) .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, excessive IOP has also been reported to be associated with other conditions such as diabetes, hypertension, obesity and metabolic syndromes (6)(7)(8)(9) . Metabolic syndromes and its components in turn, further exacerbate these conditions as it is strongly associated with insulin resistance, which plays a vital role in the development of diabetes, hypertension and obesity, and has been demonstrated in patients with BTM (12,13) . Hence, studies are required to investigate the various regulatory systems mediating IOP to understand the mechanisms underlying glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…As a common and mostly symptomless disease [2], BTM is usually diagnosed when a complete blood count has been obtained for other reasons. Besides, BTM is found to be associated with some cardiovascular risk factors such as insulin resistance and diabetes mellitus [7,8]. On the other hand, RRI is a good indicator of intrarenal hemodynamics and it has been also found to be associated with diabetes mellitus and insulin resistance [5,6,9].…”
Section: Discussionmentioning
confidence: 99%
“…This pathophysiologic mechanism may be responsible for insulin resistance and diabetes in these subjects [8]. A study on 82 BTM subjects and 82 healthy subjects showed that the development of diabetes and insulin resistance in subjects with BTM was 2 times greater than in the general population [8]. Additionally, high fasting insulin levels and insulin resistance have been reported in BTM subjects with a normal glucose tolerance [17] and high levels of fasting glucose and insulin levels have been shown in subjects with BTM [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation